Role of N6-methyladenosine methylation in head and neck cancer and its regulation of innate immune pathways - Cao, Luhong; Huang, Guixiang; Fan, Jiangang; Liu, Xingren; Ma, Zhiyue (Frontiers in Immunology, 2024)
N6-methyladenosine (m6A) is considered the most prevalent methylation modification in messenger RNA (mRNA) that critically impacts head and neck cancer (HNC) pathogenesis and development. Alterations of m6A methylation related proteins are closely related to the progression, therapeutic effect, and prognosis of HNC. The human innate immune system activates immune pathways through pattern recognition receptors, which can not only resist pathogen infection, but also play a vital role in tumor immunity. Emerging evidence has confirmed that m6A methylation affects the activation of innate immune pathways such as TLR, cGAS-STING, and NLR by regulating RNA metabolism, revealing its potential mechanisms in the innate immune response of tumor cells. However, the relevant research is still in its infancy. This review elaborates the biological significance of RNA m6A methylation in HNC and discusses its potential regulatory relationship with TLR, cGAS-STING, and NLR pathways, providing a new perspective for in-depth understanding of the role of RNA methylation in the innate immune mechanism and therapeutic application of HNC.